Formulation and evaluation of transdermal drug delivery of topiramate - Cherukuri, Suneetha; Batchu, Uma Rajeswari; Mandava, Kiranmai; Cherukuri, Vidhyullatha; Ganapuram, Koteswara Rao (International Journal of Pharmaceutical Investigation)
Background: Transdermal drug delivery system (TDDS) was designed to sustain the release and improve the bioavailability of drug and patient compliance. Among the various types of transdermal patches, matrix dispersion type systems disperse the drug in the solvent along with the polymers and solvent is allowed to evaporate forming a homogeneous drug‑polymer matrix. The objective of the present study was to design and formulate TDDS of topiramate (TPM) and to evaluate their extended release in vitro and ex vivo. Materials and Methods: In the present study, an attempt has been made to develop a matrix‑type transdermal therapeutic system comprising TPM with different ratios of hydrophilic and hydrophobic polymeric combinations using solvent casting technique. Results: The physicochemical compatibility of the drug and the polymers was studied by Fourier transform infrared spectroscopy. The results obtained showed no physical‑chemical incompatibility between the drug and the polymers. The patches were further subjected to various physical evaluations along with the ex vivo permeation studies using pig ear skin. Conclusions: On the basis of results obtained from the physical evaluation and ex vivo studies the patches containing the polymers, that is, Eudragit L 100 and polyvinylpyrrolidone, with oleic acid as the penetration enhancer were considered as the best formulations for the transdermal delivery of TPM.
Keywords: Eudragit L 100; matrix dispersion system; oleic acid; penetration enhancers; permeation studies; polyvinylpyrrolidone